O exercício do controle social pelo Conselho Estadual de Assistência Social de Goiás (2008 2012) - Ribeiro, Elizângela da Conceição (2014)
This thesis has as its objective a critically analyze of the social control category. It delimits the relevance of the struggles undertaken by social and popular movements and by a fragment of the working class in the period 1970-1980, with reason to express their rejection of the State s model of development which acted as authoritarianism and repression in respect to the working class. It subsequently won a process of democratization in the context of social rights and social control through public social policies and strictly relations the State as civil organization, made possible with the enactment of the 1988 Federal Constitution, to ensure their character. In this process of the struggle for democratization, analyzes the social control in the exercise polities of the Board of Social Welfare of Goiás and has as the question: in which political direction has the State Board of Social Work of Goiás has exercised social control? Did it exercise social control in a "democratic" form according the proposal in the PNAS/ITS 2004 permeated by the capitalist system? As methodological procedures we used a bibliographical and document research from the achievements of the State Council of Social Service of Goiás were used as procedure for methodology. In this manner, this work is organized in three chapters, which proposes a critical analysis of the exercise of social control by the State Board of Social assistance during the period 2008-2012. based on these proposal discussed, our studies of social control which proved to be a relevant issue, since demonstrated that the National Social Welfare Policy with its proposal, implementation and functionality of social control as "democratic" tool on the stage of the capitalist system social rights that restricts and limits the effective participation of its exercise, which goes in the opposite direction of the social conquests in Brazil through struggles in search of a new horizon, whereas in contemporary reproduces the control exercised by the state with the domain capital.